Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T19:34:17+02:00
X+10(12-x)-8=(10 x+12-x)1/3
x+120-10x-8=10/3x+4-1/3x
-9x+112=9/3x+4
-9x-3x=4-112
-12x=-108 ||-12
x=9
1 5 1
2010-04-15T19:35:58+02:00
X+10(12-x)-8=(10 x+12-x)1/3 /*3
3x + 30(12-x) - 24 = 10x + 12 - x
3x + 360 - 30x - 24 = 10x + 12 - x
3x - 30x - 10x + x = 12 - 360 + 24
- 36x = - 324 /: (-36)
x = 9
1 1 1
2010-04-15T19:36:47+02:00
X+ 10(12-x)-8=(10 x+12-x)1/3
x+120-10x-8=10x/3 +4 -x/3 /*3
3x +360 -30x -24=10x+12-x
336 - 12=9x + 27x
324=36x
x=9
1 1 1